Idiopathic Juvenile Osteoporosis with Progressive Kyphoscoliosis: A Case Report - Nunung Nugroho; Muhammad Faris; Albert Setiawan (JURNAL WIDYA MEDIKA, 2020)
Introduction: Osteoporosis is a common disease in elderly patients, but rarely found in children. Idiopathic juvenile osteoporosis (IJO) is one of the primary causes of childhood osteoporosis and it is a rare disease. The prevalence and pathogenesis of the disease is still not well-understood. Disease progressions may occur in patient’s without treatment causing impairment, disability and handicap to the patient. Case description: A ten-year-old boy came to specialist doctor’s clinic with pain on his back, had difficulties in wearing his pants, and a humped back posture came for a medical examination. The symptoms appeared 2 months after falling on sitting position. Radiology examinations showed progressive corpus vertebrae compression with kyphoscoliosis, no significant abnormalities in the laboratory findings. Discussion: Causes of osteoporosis were excluded through history taking, physical examination, laboratory and radiology results. Treatment of idiopathic juvenile osteoporosis still have controversies. In this case the patient showed significant improvements of symptoms after per oral vitamin D, exercises, and Jewett brace was given as the treatment. Conclusion: In this case after 1 year of treatment in physical and rehabilitation department, there is an improvement in kyphotic Cobb’s angle from 90o to 40.2o, the patient has no more limitation in doing his activities of daily living and able to do light sport activities.